Inshore Demersal Fisheries off Orissa Coast - Biswas, K. P. (Fishery Technology, 1979)
Results of bottom trawling in inshore areas off Paradeep with reference to total catch composition and catch per unit effort during 1962-1978 are reported. With increase in fishing effort, benthic species recorded the highest catch in 1969-’70 and thereafter it fluctuated. Fluctuations till 1968-’69 may be due to seasonal migration of fishes. The decline after 1971-’72 can be attributed to overfishing. Off Mahanadi, Devi and Rushikulya river mouths, showed a north-south migration of fishes from October. Presently off Devi river mouth is a rich ground for demersal fishes.